Pengaruh Literasi Keuangan, Inklusi Keuangan dan Gaya Hidup Terhadap Perilaku Keuangan Pada Generasi Milenial - Sufyati HS; Alvi Lestari (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to analyze the effect of financial literacy, financial inclusion and lifestyle on financial behavior in the millennial generation in South Jakarta. This study uses quantitative research and primary data sources with a questionnaire technique distributed to 100 respondents. Data analysis used multiple linear regression technique. The results showed that Financial Literacy (X1), Financial Inclusion (X2), and Lifestyle (X3) had a positive and significant effect on Financial Behavior (Y) in the Millennial Generation in South Jakarta. Based on the results of this study, it is hoped that the millennial generation can maintain and improve financial literacy and a good lifestyle so that their financial behavior will continue to improve.